A research review of Imam Tirmizi’s (R.A) Jami Tirmizi Compared to other Books of Hadith - Dr. Fariza Danish (Al Manhal Research Journal, 2023)
The name of Imam Tirmizi (R.A) is "Muhammad" Surname "Abu Isa". He was born in 209 AH in 824 AD in a town called Bough, which is located in the suburbs of Tirmizi. And Tirmiz is in Khorasan province of Iran. On the night of the 13th year of the third year of the year 279 Hijri, Imam Tirmizi, may God bless him and grant him peace, was married to his real owner. At that time, he was 70 years old. Your death took place in Bough, a village in the city of Tirmizi, and you are resting there now. Most of them had passed through this difficult destination, as if most of them had received the status of Hasan Qubal, "Muta' Imam Malik", "Sahih Bukhari" and Sahih Muslim, the idea of compiling another book in their presence and its beauty. It was even more difficult to get accepted, so Imam Tirmizi(R.A) made his own way apart from the previous books, and created features in his book that the previous books were devoid of. It has become, but it has also increased in terms of benefit, and it is a clear fact that "Jami Tirmizi" has a prominent place in the art of hadith and this book is a unique book of the art of hadith in which all the hadiths are collected in a jurisprudential manner. has been done In this article, the writer has mentioned the brief introduction of Sahaah Sita, the books before the Jama'ah of Imam Tirmizi(R.A) and the characteristics, virtues and conditions of Imam Tirmizi's Jama'ah Tirmizi.